Incomplete Concordance Between Host Phylogeny and Gut Microbial Community in Tibetan Wetland Birds - Bo, Tingbei; Song, Gang; Tang, Shiyu; Zhang, Mengru; Ma, Zhiwei; Lv, Hongrui; Wu, Yun; Zhang, Dezhi; Yang, Le; Wang, Dehua; Lei, Fumin (Frontiers in Microbiology, 2022)
Gut microbial communities of animals play key roles in host evolution, while the relationship between gut microbiota and host evolution in Tibetan birds remains unknown. Herein, we sequenced the gut microbiota of 67 wild birds of seven species dwelling in the Tibetan wetlands. We found an obvious species-specific structure of gut microbiota among these plateau birds whose habitats were overlapped. Different from plateau mammals, there was no strict synergy between the hierarchical tree of gut microbial community and species phylogeny. In brown-headed gulls (Larus brunnicephalus) as an example, the structure of gut microbiota differed in different habitats, and the relative abundance of bacteria, such as Lactobacillus, Streptococcus, Paracoccus, Lachnospiraceae, and Vibrio, significantly correlated with altitude. Finally, we found various pathogenic bacteria in the birds of these plateau wetlands, and the interspecific differences were related to their diet and living environments.